Religious Education for Indigenous Communities and Kepercayaan Adherents in Indonesia - Nenohai, Jear (Pascasarjana IAIN Pontianak, 2024)
Since its establishment in 2016, the Indonesian government has conducted Pendidikan Kepercayaan (Belief Education) as religious education for indigenous communities and kepercayaan (belief) adherents in Indonesia. Various studies affirm that kepercayaan Education is the Indonesian government's way of eliminating discrimination against indigenous communities and kepercayaan adherents in the educational sphere. Other research on kepercayaan Education targets the challenges of implementation in the school context. This work attempts to examine the interconnectedness of kepercayaan education and the education of indigenous religions and kepercayaan adherents within the community context. The underlying question is does belief education represent the education of indigenous religions within communities? How does the education of indigenous religions in the community context contribute to and be included in the development of kepercayaan education? As a theoretical framework, I employ the concept of indigenization that has developed in the discourse of indigenous education in Canada. The method used in this research is a literature study. The results of this study indicate that belief education does not represent the education of indigenous religions and kepercayaan adherents within the community realm. Kepercayaan education is a service designed unilaterally by the state without recognizing and respecting the diversity and educational needs of indigenous communities in Indonesia. As an alternative, I propose a reconciliation and collaboration-based indigenization approach as a new framework for reconstructing kepercayaan education. The path of reconciliation and collaboration provides a space for children of indigenous communities to achieve the national educational aspiration of learning and practicing the teachings of their 'religion' in accordance with the educational model of their respective communities.